Glass-transition-induced lattice mode shifts in PVDF and HDPE observed with terahertz time-domain spectroscopy - Wietzke, S; Jansen, C; Reuter, M; Jung, T; Kraft, D; Chatterjee, S; Koch, M (35th International Conference on Infrared, Millimeter, and Terahertz Waves, 2010)
Understanding the interactions of the crystalline and the amorphous domains in semi-crystalline polymers, such as HDPE or PVDF, is a subject of ongoing research. Here, we apply terahertz time-domain spectroscopy to study the impact of the glass transition taking place in the amorphous phase on lattice modes associated with the crystalline domains.